ANALISIS HUBUNGAN PENERAPAN LEAN MANAGEMENT DAN SIX SIGMA DENGAN EARLY PATIENT DISCHARGE SERTA IMPLIKASINYA TERHADAP PATIENT SATISFACTION DI RUMAH SAKIT UMUM DAERAH DI KALIMANTAN TIMUR - Orthega, Fanny; Azis, Musdalifah; Wardhani, Wirasmi (Penerbit Lafadz Jaya, 2026)
This study examines the effects of Lean Management and Six Sigma on Early Patient Discharge and Patient Satisfaction at one of government hospital in East Kalimantan, including the mediating role of Early Patient Discharge. A quantitative approach using PLS-SEM with SmartPLS 4.0 was employed on data from 160 healthcare and management staff respondents. Lean Management significantly influences Early Patient Discharge (β=0.292; t=3.670; p=0.000) and Patient Satisfaction (β=0.284; t=3.526; p=0.000). Six Sigma significantly affects Early Patient Discharge (β=0.483; t=6.221; p=0.000) but shows no direct significant effect on Patient Satisfaction. Early Patient Discharge has the strongest effect on Patient Satisfaction (β=0.566; t=7.505; p=0.000). Mediation analysis confirms partial mediation by Early Patient Discharge in the Lean Management–Patient Satisfaction relationship, and full mediation in the Six Sigma–Patient Satisfaction relationship. R² values indicate moderate to strong predictive power. These findings highlight that optimizing the patient discharge process is a key strategy for improving patient satisfaction.